Uma análise da pandemia do coronavírus (covid-19) na região do vale do Jaguaribe no estado do Ceará - Silva, Jefferson Rebouças (Universidade Federal Rural do Semi-Árido, 2020)
In December 2019, the city of Wuhan, China, notified the World Health Organization (WHO) that it was experiencing an outbreak of pneumonia, as those infected had symptoms similar to that disease. After a series of investigations into this outbreak, a new Coronavirus family has been identified, called Sars-Cov-2. Faced with an accelerated spread of the virus worldwide, on March 11, 2020, WHO began treating this outbreak as a pandemic. In Brazil, the first case of Coronavirus was confirmed on February 26, 2020, in the city of São Paulo, arriving in the Northeast in March 2020, more precisely in Bahia. The virus arrived in Ceará on March 15, 2020, in the capital Fortaleza, and subsequently in the Mesoregion of Vale do Jaguaribe on April 3, 2020, where the first case of the disease was confirmed in the municipality of Jaguaribe. In this context, the objective of this work is to analyze the first semester of the Covid-19 pandemic in the Vale do Jaguaribe Mesoregion, located in the state of Ceará, in order to present the relationships between the behavior of the contagion index and the preventive measures adopted in its 15 municipalities. The data were collected on the websites of state and municipal governments, and based on their interpretation, it was possible to determine the cities in the studied Mesoregion that had the largest number of confirmed cases and deaths caused by Covid19. Regarding the incidence rate, the municipality of Palhano can be positively highlighted as having the lowest rate among the analyzed municipalities in the region, with a rate of 1,076.1, and as a negative highlight, the municipality of Jaguaretama with a rate of 4,377.3. Regarding lethality, the municipality with the lowest value was Iracema, with 1.05%, and the one with the highest rate was Palhano, with 3.96%.
Monografia
Keywords: Pandemia; Covid-19; Coronavírus; Ceará; Vale do Jaguaribe; Pandemic; Covid-19; Coronavirus; Ceará; Vale do Jaguaribe; ENGENHARIAS::ENGENHARIA DE PRODUCAO